PENGARUH MINAT BELAJAR MATEMATIKA DALAM PEMBELAJARAN DARING TERHADAP PRESTASI BELAJAR SISWA MAN 1 SRAGEN - Firsta Adira; Lina Latifah (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2022)
Mathematics learning that takes place online causes students' interest and motivation to decrease. This can cause student achievement to also decrease. This study aims to determine the influence of student interest in learning mathematics online on the results of student achievement. The type of this research is quantitative research with the research subjects are the students of class XI MAN 1 Sragen, totaling 22 students. The data collection technique uses questionnaires and documentation of student achievement through the results of the Mid-Semester Examination for the Academic Year 2021/2022. The technical analysis of the data used in this research is the regression correlation test with the help of the SPSS version 24 computer program and the help of Ms. Excel. The results showed that some students who had a high interest in learning were not supported by good learning achievements. Thus, there is no significant effect between student interest in mathematics learning on student achievement in class XI MAN 1 Sragen.